NUMERICAL ANALYSIS OF THE EFFECT OF IMPLANT GEOMETRY TO STRESS DISTRIBUTIONS OF DENTAL IMPLANT SYSTEM - Abubekir Eltas; Murat Solmaz; Serkan Dündar; Tolga Topkaya (Cumhuriyet University, 2015)
ABSTRACT Purpose: The success of dental implants is related to the quality, quantity of local bones, implant design and surgical technique. Implant diameter and length are accepted as key factors. Present work focuses to investigate the effect of titanium implant geometry to stress distributions in implant system.Materials and Methods: For this purpose three different implant models which are currently being used in clinical cases constructed by using ANSYS Workbench 12.1. The stress distributions on components of implant system  under static loadings were analyzed for all models.Results: The maximum stress values that occurred in all components happen in the case of loading in which the Nucleoss T-4 implant is used, but the occurred lowest stress values happen in the case of Fı loading in which Nobel Active  implant is used. In all models, the maximum tensions have occurred in the neck region of the implants.Conclusion: The crested loss of bones in the neck region of the implants lessen the long-term survival rate of implants.The lengt and the size of the implant are the two important factors in the stress distribution.